Increased blood lactate is prevalent and identifies poor prognosis in patients with acute heart failure without overt peripheral hypoperfusion. (12th February 2018) - Zymliński, Robert; Biegus, Jan; Sokolski, Mateusz; Siwołowski, Paweł; Nawrocka‐Millward, Sylwia; Todd, John; Jankowska, Ewa A.; Banasiak, Waldemar; Cotter, Gad; Cleland, John G.; Ponikowski, Piotr
Abstract : Aims: Lactate is produced by anaerobic metabolism and may reflect inadequate tissue perfusion in conditions such as acute heart failure (AHF). We evaluated the prevalence and clinical significance of elevated blood lactate on admission in patients with AHF. Methods and results: We enrolled 237 patients with AHF (mean age 67 ± 12 years; 70% men) presenting without overt clinical evidence of peripheral hypoperfusion ('warm haemodynamic profile'). Median (upper and lower quartiles) blood lactate on admission was 1.8 (1.5; 2.4) mmol/L; 103 (43%) patients had an elevated blood lactate (≥2 mmol/L). Patients with an elevated lactate had higher blood high‐sensitivity troponin I [15.4 (8.5; 26.1) vs. 9.9 (4.3; 19.6) pg/mL], aspartate aminotransferase [28 (20; 44) vs 24 (19; 36) IU/L] and endothelin‐1 (12.1 ± 6.2 vs. 9.3 ± 3.9 pg/mL) (all P < 0.05). In this group plasma concentration of neutrophil gelatinase‐associated lipocalin increased during the first 48 h, whereas values fell for those with normal baseline lactate [1.9 (–3.2; 9.7) vs. –1.3 (–13.9; 5.6) μg/dL; P < 0.05). One‐year mortality was higher amongst patients with an elevated blood lactate (36% vs. 21%; P < 0.05). After adjustment for other well‐established prognostic variables, blood lactate on admission predicted poor outcome (hazard ratio 1.24, 95% confidence interval 1.08–1.41; P < 0.05). Conclusions: An elevated blood lactate on admission is common in AHF patients without overt clinical evidence of peripheral hypoperfusion and is associated with markers of organ dysfunction/damage and a worse prognosis.